Group Guidance Using Educational Cinema Techniques to Improve Understanding of Hate Speech - Anna Annisa Andriani; Ayu Elsyawela; Aisyah Nofin Nuraini; Anggyta Dinda Wijaya; Asep Solikin; M. Fatchurrahman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study aims to assess the effectiveness of peer guidance services in enhancing self-confidence among adolescents. The service was delivered to 9th-grade students of SMP Negeri 12 Palangka Raya as part of a psychosocial intervention. This research employed a pre-experimental method with a one-group pretest-posttest design. The sample consisted of 12 students selected using purposive sampling. The instrument used was a validated and reliable self-confidence scale. The findings revealed an increase in mean scores from pre-test to post-test. The Wilcoxon test using SPSS 25 resulted in a significance value of 0.002 (<0.05), indicating that peer guidance is effective in increasing students' self-confidence. Thus, peer counseling can serve as a strategic alternative to support adolescents' psychological development in schools.